Interest Rates and Equity Extraction During the Housing Boom - Bhutta, Neil; Keys, Benjamin J. (American Economic Review, 2016)
Credit record panel data from 1999–2010 indicates that the likelihood of home equity extraction (borrowing, on average, about $40,000 against one's home) peaked in 2003 when mortgage rates reached historic lows. We estimate a 27 percent rise in extraction in response to a 100 basis point rate decline, and that house price growth amplifies this relationship. Differential responses to interest rates and home price appreciation by borrower age and credit score provide new evidence of financial frictions. Finally, equity extractions are associated with higher default risk, consistent with the use of borrowed funds for consumption or illiquid investment. (JEL D14, E43, E52, G12, R31)